Peramalan Harga Emas Antam : Pendekatan Metode Dekomposisi ARIMA dan Model ARCH-GARCH - Surahman, Fikri; Prilistiana, Indi; Mutiara Sinaga, Vhania; Agustina, Neli (Yayasan Daarul Huda Kruengmane, 2025)
Gold is one of the precious metals that serves as a standard medium of financial exchange in various countries. Additionally, gold is used as an asset for investment purposes. This is due to its zero-inflation characteristic, which acts as a hedge against inflation and economic uncertainty. Antam gold is one type of gold that attracts high interest from both investors and the general public. However, the fluctuating price of Antam gold requires investors to continuously monitor its price movements.This study aims to predict the value of Antam gold from January 13 to January 31, 2025, using the ARIMA decomposition and ARCH-GARCH methods. Based on the research findings, the predicted price of Antam gold for the given period shows an increasing trend. The decomposition-ARIMA (1,1,1) method, which integrates time series decomposition into trend, seasonal, cyclical, and random components while applying ARIMA to the random component, is identified as more accurate than the GARCH(1,0) model. This is evidenced by the MAPE value of the decomposition-ARIMA model, which is 0.185%, slightly better than the GARCH model at 0.898%.